2021
DOI: 10.2147/phmt.s321536
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Safety of High Flow Nasal Cannula in Pediatric Intensive Care Unit: Retrospective Single Center Experience in Saudi Arabia

Abstract: Background: High flow nasal cannula (HFNC) is a new device for respiratory support. Its use continues to increase in pediatrics as its system is easily set up and well tolerated by patients. We aimed in this study to explore indications and safety of HFNC use and predictors of HFNC failure. Methods: Hospital records of 92 children with acute respiratory distress admitted to the pediatric intensive care unit (PICU) in Abha Maternity and Children Hospital from January 2018 until March 2020 and received HFNC ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The failure of HFNC was found in one fourth of the patients participated in the study. 1 However, we believe certain aspects of this study need to be addressed.…”
Section: Dear Editormentioning
confidence: 98%
See 2 more Smart Citations
“…The failure of HFNC was found in one fourth of the patients participated in the study. 1 However, we believe certain aspects of this study need to be addressed.…”
Section: Dear Editormentioning
confidence: 98%
“…We have read with great interest the article published by Asseri et al which explores the indications and safety of high flow nasal cannula (HFNC) use in Pediatric Intensive Care Unit (PICU) and determine the predictors of its failure in Saudi Arabia. 1 The study identified positive clinical characteristics and laboratory tests in most of the children after 8 hour of the use of HFNC in pediatric patients and the main indications used were respiratory distress secondary to bronchopneumonia, bronchiolitis, status asthmaticus, and post-extubation. The failure of HFNC was found in one fourth of the patients participated in the study.…”
Section: Dear Editormentioning
confidence: 98%
See 1 more Smart Citation
“…Most infants with severe pneumonia experience hypoxemia and dyspnea, necessitating effective mechanical respiratory support. A substantial body of research indicates that high-flow nasal cannula (HFNC) therapy can reduce intubation and mortality rates in infants and children with an oxygenation index (PaO 2 /FiO 2 ratio, P/F ratio) below 200 mmHg [ 1 , 2 ]. Recently, HFNC therapy has gained increasing prominence in pediatric intensive care units (PICUs), demonstrating effectiveness in improving oxygenation and reducing the need for tracheal intubation in infant and pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, HFNC therapy is not without its failures. Factors predictive of HFNC therapy failure include underlying chronic disease, low diastolic blood pressure, high respiratory and heart rates, and elevated initial PaCO 2 levels [ 2 ].…”
Section: Introductionmentioning
confidence: 99%